Roles of chlorophyllin in cell proliferation and the expression of apoptotic and cell cycle genes in HB4a non-tumor breast cells - D´Epiro, Gláucia Fernanda Rocha; Semprebon, Simone Cristine; Niwa, Andressa Megumi; Marcarini, Juliana Cristina [UNESP]; Mantovani, Mário Sérgio (My University, 2016)
Chlorophyllin (Chl) has attracted interest in the scientific community due to its chemopreventive and antimutagenic properties. However, the molecular mechanisms of action of Chl remain unclear. This study assesses the effects on cell proliferation and the expression of genes involved in apoptosis, and the cell cycle in HB4a cells treated with Chl. Chl was cytotoxic and induced apoptosis to HB4a cells at 400 μg/mL. Analysis of gene expression showed that there was a decrease in the mRNA level of BIRC5 and CCNA2 genes involved in apoptosis and cell cycle progression, respectively. The proapoptotic gene BAX and the antiapoptotic genes BCL-2 and BCL-XL were upregulated. The cytotoxicity of Chl has been attributed to increases in the expression of BAX and decreases in the expression of genes involved in the cell cycle, but increases in the expression of anti-apoptotic genes suggests a mechanism for protection from cell death induced by Chl. This study provides important information about mechanisms that protect against or trigger damaging processes in non-tumor cells.
Keywords: Apoptosis; cell cycle; cytotoxicity; gene expression